(untitled) (Agronomy Journal of Nepal, 2021)
Consequences generated by climate change disasters in the vulnerable agricultural system of Nepal could increase in coming days in the absence of effective adaptation strategies in the both agriculture and livestock sector. There is growing evidence that forage and fodder production activity can be a potential adaptation strategy, but adopted in a limited scale. The objective of this study was to identify the determinants of forage and fodder production activity by livestock farmers in the Terai region of Nepal. Primary data collected through household survey of 600 households, 100 from each district in Morang, Sarlahi, Bara, Chitwan, Rupandehi and Banke were analyzed using logistic regression technique. Results showed that western Terai dummy and family size were negatively affecting the adoption of forage and fodder production. Whereas access to credit, size of livestock holding and training were positively and significantly affecting the adoption of the forage and fodder production activity. The magnitude of effect of these significant variables are western Terai dummy (25.2%), family size (92.60%), access to credit dummy (74.21%), size of livestock holding (10.8%) and training dummy (188.80%). Findings of the study suggested that provided opportunity to dairy farmers for participation in training on livestock production management practices and increased access to credit for making investment in dairy enterprises. Rearing livestock at commercial scale also motivates dairy farmers to produce forage and fodder in their own farm land. It is also recommended to provide lease- in land system for dairy farmers with large size family to grow forage and fodder crops aside from promotional activities are needed in western Terai region of the country in particular.